Empathy for Nature: Exploring interdisciplinary collaborations in the Arts - (:unkn) unknown (My University, 2023)
This book presents a comprehensive exploration of fourteen collaborative interdisciplinary artistic projects, implemented by the partners of EMPACT in a period between June and December 2023, that explored the intricate connection between artistic expression and disciplines such as philosophy, architecture, urban planning, biology and anthropology. The thematic of the collaborations, centered on cultivating empathy for nature and non-human beings and advancing sustainability, underscores the strenuous efforts of inspired artists working on various artistic genres. This book not only offers a glimpse into the diverse and fascinating collaborations between artists and experts from non-artistic disciplines but also prompts reflection on the significance of collaborative art itself. As we navigate through these collaborative projects, we are reminded of the vital role of collaborative endeavours in addressing the complex challenges of climate-change and advancing our shared commitment to empathy, sustainability, and a harmonious coexistence with nature.
Keywords: Empathy; Visual arts; Interdisciplinary collaborations